Cascading Adjacent Level Vertebral Compression Fractures Necessitating a Series of Eleven Kyphoplasties - Evan Curatolo; Matthew Reuter; Adil Samad; Daniel Flynn; Marc Menkowitz; Steve Paragioudakis (Case Reports in Orthopedics)
Vertebral kyphoplasty is a procedure used for the treatment of compression fractures. While early randomized-controlled trials were equivocal regarding its benefits, more recent RCTs have shown favorable results for kyphoplasty with regard to pain relief, functional recovery, and health-care related quality of life compared to control patients. Risks of kyphoplasty include but are not limited to cement extrusion, infection, hematoma, and vertebral body fracture of adjacent levels. We describe a case of a 66-year-old male attorney who underwent eleven kyphoplasties in an approximately one-year period, the majority of which were for fractures of vertebrae adjacent to those previously treated with kyphoplasty. Information on treatment was gathered from the patient’s hospital chart and outpatient office notes. Following the last of the eleven kyphoplasties (two at T8, one each at all vertebrae from T9 to L5), the patient was able to function without pain and return to work. His physiologic thoracic kyphosis of 40 degrees prior to the first procedure was maintained, as were his lung and abdominal volumes. We conclude that kyphoplasty is an appropriate procedure for the treatment of vertebral compression fractures and can be used repeatedly to address fractures of levels adjacent to a previous kyphoplasty.